Pengembangan Bahan Ajar E-Modul Berbasis Flip PDF Professional untuk Meningkatkan Kemampuan Koneksi Matematis - Novianti Novianti; Asrul Karim (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
Mathematical connection ability is one of the important competencies that need to be developed so that students are able to relate mathematical concepts to other mathematical concepts, other fields of science, and the context of everyday life. However, in reality, the mathematical connection ability of elementary school students is still relatively low, one of which is caused by the limitations of conventional teaching materials and the lack of utilization of interactive digital technology. This study aims to develop teaching materials in the form of Flip PDF Professional-based e-modules on the material of flat shapes, and to test their validity and effectiveness in improving the mathematical connection ability of elementary school students. The research method used is research and development with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of the research trial involved fifth-grade students of UPTD SD Negeri 2 Peusangan Siblah Krueng. The research instruments included expert validation sheets, student response questionnaires, and mathematical connection ability tests. The validation results showed that the developed e-module was in the very feasible category based on the assessment of media, material, and language experts. The results of the product trial also showed a very positive response from students. The effectiveness test using the N-gain calculation showed a value of 0.82, a high score, indicating that the Flip PDF Professional-based e-module is effective in improving students' mathematical connection skills. Therefore, the Flip PDF Professional-based e-module is feasible and effective for use as a digital teaching material in elementary school mathematics.